Framework for selecting best practices in public health: a systematic literature review - Eileen Ng; Pierpaolo de Colombani (SAGE Publishing, 2015)
Evidence-based public health has commonly relied on findings from empirical studies, or research-based evidence. However, this paper advocates that practice-based evidence derived from programmes implemented in real-life settings is likely to be a more suitable source of evidence for inspiring and guiding public health programmes. Selection of best practices from the array of implemented programmes is one way of generating such practice-based evidence. Yet the lack of consensus on the definition and criteria for practice-based evidence and best practices has limited their application in public health so far. To address the gap in literature on practice-based evidence, this paper hence proposes measures of success for public health interventions by developing an evaluation framework for selection of best practices. The proposed framework was synthesised from a systematic literature review of peer-reviewed and grey literature on existing evaluation frameworks for public health programmes as well as processes employed by health-related organisations when selecting best practices. A best practice is firstly defined as an intervention that has shown evidence of effectiveness in a particular setting and is likely to be replicable to other situations. Regardless of the area of public health, interventions should be evaluated by their context, process and outcomes. A best practice should hence meet most, if not all, of eight identified evaluation criteria: relevance, community participation, stakeholder collaboration, ethical soundness, replicability, effectiveness, efficiency and sustainability. Ultimately, a standardised framework for selection of best practices will improve the usefulness and credibility of practice-based evidence in informing evidence-based public health interventions.